The application of the integrated course on ocular anatomy in the standardized training teaching of ophthalmology residents - LI Zuohong; TANG Biting; WANG Kerui; ZOU Yuxian; LIANG Xuanwei; MAO Zhen (Yanke Xuebao)
[Objective:] To explore and evaluate the application and effect of an integrated ocular anatomy course comprising three main components: ‘online preview,’ ‘lecture,’ and ‘Wetlab dissection training’in the standardized training teaching of ophthalmology residents (hereinafter referred to as ‘resident training’). [Methods:] A total of 93 new resident trainees from Zhongshan Ophthalmic Center of Sun Yat-sen University in 2023 were included in the integrated course on ocular anatomy during pre-job training. Tests were carried out before and after the course to evaluate the teaching effect of the course, and questionnaires were issued after the course to investigate the satisfaction of the course. It adopts the form of anonymous offline test and satisfaction questionnaire. [Results:] The median total scores before (T1) and after (T2) training were 60 and 70, respectively; the lowest scores, 25%, 75% and highest scores of T1 were 10, 40, 62.5 and 90, respectively; the lowest scores, 25%, 75% and highest scores of T2 were 30, 60, 80 and 100, respectively, and the scores of T2 were significantly higher than those of T1 (P<0.000 1). The mean confidence of T1 and T2 were 26.53±5.08 and 31.83±4.02, respectively (P<0.001). Participants generally expressed satisfaction with the integrated programme. [Conclusions:] After receiving the training of the integrated course, the students' mastery of the knowledge of ocular anatomy has been significantly improved, and the satisfaction of the integrated course is high. The integrated course on ocular anatomy is effective, and it is a teaching reform with popularization significance.